Mathematical modeling of the influence of interfering species on the performance of an amperometric biosensor with porous membrane - Stonkienė, Liana; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2014)
This paper presents a one-dimensional-in-space mathematical model of the amperometric biosensor with porous membrane influenced by the presence of interfering species. The model is based on diffusion equations. Various effects regarding amperometric bias, caused by the presence of interfering species, have been analyzed.